Effects of Nitrogen on Mesophyll Cell Division and Epidermal Cell Elongation in Tall Fescue Leaf Blades - MacAdam, Jennifer W. (1989)
Leaf elongation rate (LER) in grasses is dependent on epidermal cell supply (number) and on rate and duration of epidermal cell elongation. Nitrogen (N) fertilization increases LER. Longitudinal sections from two genotypes of tall fescue (Festuca arundinacea Schreb.), which differ by 50% in LER, were used to quantify the effects of N on the components of epidermal cell elongation and on mesophyll cell division. Rate and duration of epidermal cell elongation were determined by using a relationship between cell length and displacement velocity derived from the continuity equation. Rate of epidermal cell elongation was exponential. Relative rates of epidermal cell elongation increased by 9% with high N, even though high N increased LER by 89%. Duration of cell elongation was approximately 20 h longer in the high- than in the low-LER genotype regardless of N treatment. The percentage of mesophyll cells in division was greater in the high- than in the low-LER genotype. This increased with high N in both genotypes, indicating that LER increased with cell supply. Division of mesophyll cells adjacent to abaxial epidermal cells continued after epidermal cell division stopped, until epidermal cells had elongated to a mean length of 40 micrometers in the high-LER and a mean length of 50 micrometers in the low-LER genotype. The cell cycle length for mesophyll cells was calculated to be 12 to 13 hours. Nitrogen increased mesophyll cell number more than epidermal cell number: in both genotypes, the final number of mesophyll cells adjacent to each abaxial epidermal cell was 10 with low N and 14 with high N. A spatial model is used to describe three cell development processes relevant to leaf growth. It illustrates the overlap of mesophyll cell division and epidermal cell elongation, and the transition from epidermal cell elongation to secondary cell wall deposition.